2019
DOI: 10.1093/trstmh/trz029
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with completion of childhood immunization in Malawi: a multilevel analysis of the 2015–16 Malawi demographic and health survey

Abstract: Background Between 2010 and 2015, the percentage of children 12–23 months of age who received full immunization in Malawi decreased from 81% to 76%, prompting us to investigate the factors associated with completion of childhood immunization in Malawi. Methods Using data from the 2015–16 Malawi Demographic and Health Survey, generalized linear mixed models were applied on 3145 children 12–23 months of age nested within 850 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Children from medium- and high-wealth households were more likely to complete their vaccination than children from poor households. this finding is in line with studies done in Maynamar [ 33 ], Malawi [ 38 ], Democratic Republic of Congo [ 35 ], sub-Saharan Africa [ 23 ], and Ethiopia [ 21 ]. The possible explanation might be due to wealthier people have healthier childcare practices and better health-seeking behavior, or travel cost to health facilities can restrict poor people’s willingness to immunize their children [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Children from medium- and high-wealth households were more likely to complete their vaccination than children from poor households. this finding is in line with studies done in Maynamar [ 33 ], Malawi [ 38 ], Democratic Republic of Congo [ 35 ], sub-Saharan Africa [ 23 ], and Ethiopia [ 21 ]. The possible explanation might be due to wealthier people have healthier childcare practices and better health-seeking behavior, or travel cost to health facilities can restrict poor people’s willingness to immunize their children [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous findings from the United States show that under vaccination was more likely in male than female children [ 21 ]. Similarly, studies conducted in African countries indicated that children born to mothers with no formal education, children who resided in the poorest households [ 22 ], children whose households reported distance to the nearest health facility as a big problem, children whose delivery occurred in a non-health facility, and children who had no health card were more likely to be non- and under-vaccinated [ 23 , 24 ]. More importantly, the findings uncover new evidence by demonstrating that neighbourhood and country-level factors influence non-vaccination for polio above and beyond individual level factors.…”
Section: Discussionmentioning
confidence: 99%
“…ere is both direct and indirect cost associated with immunization updates such as transportation to the nearest point to receive the services [26]. As a result, mothers from wealthier families may have a better chance of getting modern health care for their families, especially their children, implying greater liberty [27]. Children of mothers in the poorest wealth quintile, on the other hand, are less likely to fully vaccinate their children due to difficulty in access to facilities such as transportation fees [27].…”
Section: Discussionmentioning
confidence: 99%